What happened to the Galatian Christians? Paul's legacy in Southern Galatia - Cilliers Breytenbach (Acta Theologica)
Paul’s Letter to the Galatians points to the influence of his missionary attempts in Galatia. By reconstructing the missionary journeys of Paul and his company in Asia Minor the author argues once again for the south Galatian hypothesis, according to which the apostle travelled through the south of the province of Galatia, i.e. southern Pisidia and Lycaonia, and never entered the region of Galatia proper in the north of the province. Supporting material comes from the epigraphic evidence of the apostle’s name in the first four centuries. Nowhere else in the world of early Christianity the name ?????? was used with such a high frequency as in those regions where the apostle founded the first congregations in the south of the province Galatia and in the Phrygian-Galatian borderland.